Effect of Probiotic Extracted from Lactobacillus Sp. Antagonist Helicobacter pylori of Human Stomach Ulcer - Ghydaa H. Aljeboury (Journal of Global Pharma Technology, 2016)
Total of (130) samples of stomach ulcer were collected from patients suffering from peptic ulcer who visited three different hospitals in Baghdad. After testing the sensitivity test against Helicobacter pylori against 10 antibiotics, the sensitivity test for 10 antibiotics demonstrated the efficacy of the antibiotic cephotaxim and rifampicin in the elimination of the bacteria. According to the results of the sensitivity test, one of the isolates of the Helicobacter pylori 4 (HpG 4) was chosen for being resistant to all antibiotics (except amoxicillin). Two isolates of Lactobacillus acidophilus, Lactobacillus plantarum were selected based on their high inhibitory activity against Helicobacter pylori growth bacteria for subsequent experiments .The minimum inhibitory concentration of Lactic Acid Bacteria concentrated filtrate was performed for three times .The concentrated filtrate showed the efficacy in minimizing and inhibiting the growth of pathogenic bacteria Helicobacter pylori. So the aim of the study was to discover the role of probiotics in the treatment of Helicobacter pylori infection and study of effect of probiotic on reducing Helicobacter pylori stomach ulcer as supporting and safer. Keywords: Human Stomach Ulcer; Probiotic Extracted; Lactic Acid Bacteria